2013
DOI: 10.1186/1756-9966-32-10
|View full text |Cite
|
Sign up to set email alerts
|

microRNA response elements-regulated TRAIL expression shows specific survival-suppressing activity on bladder cancer

Abstract: BackgroundBladder transitional cell carcinoma greatly threatens human health all over the world. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) shows a strong apoptosis-inducing effect on a variety of cancer cells including bladder cancer. However, adenovirus-mediated TRAIL expression still showed cytotoxicity to normal cells mainly due to lack of tumor specificity.MethodsTo solve the problem, we applied miRNA response elements (MREs) of miR-1, miR-133 and miR-218 to confer TRAIL expression wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…It is well documented that TRAIL induces apoptosis via microRNA regulation [45] including miR34a/ [46] or miR-494 [47] in cancer cells. Thus, Farooqi et al [3] suggested that miRNA regulation of TRAIL-mediated signaling in prostate cancer cells can provide potential biomarkers for the characterization of patients as responders and non-responders for TRAIL-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that TRAIL induces apoptosis via microRNA regulation [45] including miR34a/ [46] or miR-494 [47] in cancer cells. Thus, Farooqi et al [3] suggested that miRNA regulation of TRAIL-mediated signaling in prostate cancer cells can provide potential biomarkers for the characterization of patients as responders and non-responders for TRAIL-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in vivo data revealed that Ad-TRAIL-MRE-7-122 suppressed the growth of Bcap37 tumors in mice as potent as Ad-TRAIL and had no hepatotoxicity to the animals. In fact, the similar effects have been verified in some other types of cancers using MRE-based strategy, such as melanoma, glioma and bladder carcinoma [11][12][13].…”
Section: Discussionmentioning
confidence: 59%
“…More importantly, the expression of inserted genes can be suppressed in normal cells because of the overexpression of selected miRNAs. However, no publication that focuses on the MRE-regulated gene therapy for breast cancer is available, although this strategy has been tested for some other types of cancer [11][12][13][14].…”
mentioning
confidence: 99%
“…It is appropriate to mention that miRNA subsets under-expressed in cervical cancer cells can be used to regulate the proficiency of cancer-specific adenoviral vector that expressed TRAIL based on miRNA response elements (MREs) of miRNAs whose levels were reduced in cervical cancer. Similar approaches have been tested using in bladder cancer and glioma using adenoviral vector expressing TRAIL and introducing MREs of miRNA subsets down-regulated in respective cancer cells [185,186]. …”
Section: Resultsmentioning
confidence: 99%